The number of metastatic lymph nodes optimizes staging in patients aged 55 years or older with papillary thyroid cancer - Sun, Yun-Gang; Chen, Fei; Sun, Qiao-Ling; Tian, Jin-Yu; He, Xiao-Chuan (Frontiers in Endocrinology, 2022)
Purpose: Current staging criteria for papillary thyroid cancer (PTC) do not include the number of metastatic lymph nodes (LNs), which is highly predictive of survival in multiple cancers. The LN metastasis burden is particularly relevant for older adults with thyroid cancer because of their poor prognosis. We examined a modified staging system for this population utilizing node number (Nn). Methods: Overall, 14,341 patients aged 55 years or older with stage Ⅰ-ⅣB PTC were identified in the 2004–2015 Surveillance, Epidemiology and End Results database. Cox regression models were conducted to test the relationship between positive LN number and PTC-specific survival (PTCSS). Independent training/validation sets were used to derive and validate a new revised TNnM grouping. The 8th edition American Joint Committee on Cancer TNM staging system was compared with TNnM stage by calculating the 10-year PTCSS rates, Harrell’s concordance index (C-index), and Akaike’s information criterion (AIC). Results: An increase in number of LN metastases was identified as an independent, negative prognostic factor for PTCSS in multivariate analysis. 10-year PTCSS for stage I-ⅣB based on the AJCC 8th edition TNM were 98.83%, 93.49%, 71.21%, 72.95%, and 58.52%, respectively, while 10-year PTCSS for the corresponding stage in the TNnM were 98.59%, 92.2%, 83.26%, 75.24%, and 56.73%, respectively. The revised TNnM stage was superior, with a higher C-index and a lower AIC in both the training and validation cohorts. Conclusion: The TNnM staging system for PTC patients ≥ 55 years could be associated with improved outcomes. External validation studies of this system are warranted.